MOTIVATION AS A KEY FACTOR IN IMPROVING THE EFFICIENCY OF MANAGEMENT SYSTEMS IN THE RESTAURANT BUSINESS - STADNYTSKA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the importance of motivation as a key factor in enhancing the efficiency of management systems within restaurant enterprises. The study provides a comprehensive analysis of theoretical approaches to understanding motivation, including classical, behavioral, and modern concepts. It is emphasized that staff motivation in the restaurant business should be viewed as a continuous process of aligning organizational objectives with the personal and professional needs of employees. Both material and non-material motivators are considered — from financial incentives, bonuses, and career advancement to recognition, corporate culture, psychological comfort, and participation in decision-making. The research identifies key factors influencing employee motivation in the restaurant industry: working conditions, leadership style, internal communication, and social climate. The article underlines that the lack of an effective motivation system leads to staff turnover, reduced productivity, and lower quality of service, which directly affects the institution’s reputation and profitability. Special attention is given to the challenges of motivating restaurant personnel in the Ukrainian context, including limited financial resources, staff shortages, and the need to adapt Western management models to domestic realities. The author proposes practical recommendations for improving the motivation system — implementing a balanced mix of tangible and intangible incentives, introducing transparent evaluation criteria, investing in staff development, and fostering a positive organizational culture. The results of the study demonstrate that an effectively designed motivation mechanism increases labor productivity, employee loyalty, and customer satisfaction, thereby contributing to the sustainable development and competitiveness of restaurant enterprises.